Subsídios à agricultura no comércio internacional: teoria, regulação e prática - Bruno, Flávio Marcelo Rodrigues (Universidade do Vale do Rio dos Sinos, 2010)
This study examined the practice of agricultural subsidies in international trade, being conceived on the foundations of the movement of the interdisciplinary Law and Economics. Designed based on bibliographical studies and statistics on international trade scenario, the main objective scale the practice of subsidies as a tool primarily economic strategy for the agricultural sector, especially to the United States and the European Union. The doctrine states that the ultimate economic impact of subsidies is causing distortions in international trade and ensures that in practice it has proved. This study dimensions such statements, trying to understand how the doctrine came to this conclusion and for what reasons these effects are felt in the practice of international trade. A complete ban on subsidies is not desirable because its practice, in essence, is an alternative to seeking the welfare of the nation. However, the use of subsidies, how they are being charged, especially those given to agriculture, are formed in nature protectionist interventions that distort international trade. One can identify the United States and European Union nations as they use most of subsidies in international trade, given the amount of registered cases in the WTO involving the two nations as the defendant in respect of countervailing duties to the practice of subsidizing. It was demonstrated that the levels of subsidies to the agricultural sector remain at a high level, a factor that has raised concerns about the effectiveness of international rules aimed at regulating their practice. It was identified that there was a considerable increase of trade disputes relating to countervailing duties in relation to total trade disputes involving agricultural sector. It was demonstrated that the United States and the European Union economies they use most of this trade policy instrument to intervene in international trade, examining two most notorious cases for these two economies that have been submitted to the WTO, which involve the granting subsidies in the performance of these nations in international agricultural trade.
Keywords: WTO; Agricultural subsidies; International trade; Subsidies; OMC; Subsídios agrícolas; Comércio internacional; Subsídios; ACCNPQ::Ciências Sociais Aplicadas::Economia